Bacterial Foraging-Based Solution to the Unit-Commitment Problem - Eslamian, M.; Hosseinian, S.H.; Vahidi, B. (IEEE transactions on power systems, 2009)
The unit commitment (UC) problem is one of the most difficult optimization problems in power system, because this problem has many variables and constraints. The objective is the minimization of the total production cost over the scheduling horizon while the constraints must be satisfied, too. This paper employs a new evolutionary algorithm known as bacterial foraging (BF) for solving the UC problem. This new integer-code algorithm is on the base of foraging behavior of E-coli Bacteria in the human intestine. By integer coding of the problem, computation time decreases and the minimum up/down-time constraints may be coded directly, and therefore, there is no need to use penalty functions for these constraints. From simulation results, satisfactory solutions are obtained in comparison with previously reported results.